Heart rhythm disorders and cardiorehabilitation: the role of kinesiophobia - Amelina Тетяна; Polishchuk Олександр (Psychosomatic Medicine and General Practice, 2021)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" II Congress. It is dedicated to the role of kinesiophobia in heart rhythm disorders and cardiorehabilitation.